2006
DOI: 10.1515/ijamh.2006.18.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy in the treatment of alcohol and substance abusing adolescents with suicidal behavior

Abstract: Adolescence is a unique time period in an individual's life, one in which suicide and substance abuse become substantial health risks. Currently, suicide accounts for approximately 14% of all deaths among 15-24 year olds in the USA. Drug, alcohol abuse and dependence are the most prevalent causes of adolescent morbidity and mortality in the USA. Numerous studies have demonstrated the link between adolescent alcohol, substance abuse and suicide. When compared to community controls, the rate of a substance abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
(14 reference statements)
1
9
0
1
Order By: Relevance
“…This finding is consistent with numerous previous studies that reported a significant correlation between substance use and suicide in adolescents (Conason et al 2005;Mehlenbeck et al 2003). This finding is explained by the gateway theory of substance use.…”
Section: Discussion and Implications For Social Work Practicesupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with numerous previous studies that reported a significant correlation between substance use and suicide in adolescents (Conason et al 2005;Mehlenbeck et al 2003). This finding is explained by the gateway theory of substance use.…”
Section: Discussion and Implications For Social Work Practicesupporting
confidence: 93%
“…It has been proven by several studies that there is a significant correlation between substance use and suicide among adolescents (Conason et al 2005;Mehlenbeck et al 2003). Studies have consistently demonstrated that suicidal behaviors are more likely to occur among adolescents who abuse alcohol (Bae et al 2005;Shaffer and Pfeffer 2001) or use illicit drugs (Gould et al 2003;King et al 2001).…”
Section: Substance Use and Suicidementioning
confidence: 99%
“…And despite the strong association between adolescent substance use and suicidal behaviors, few studies have investigated the effectiveness of combined interventions for these two problems (Conason, Oquendo, & Sher, 2006). Because the presence of a substance use disorder is significantly associated with readmission of adolescents to inpatient care (Fontanella, 2008), it is imperative that inpatient psychiatric facilities take action to adequately address substance use issues when they present in adolescents admitted due to suicidal behavior.…”
Section: Adolescent Inpatient Psychiatric Care: a Missed Opportunity mentioning
confidence: 99%
“…L'hypothèse selon laquelle la consommation de SPA causerait des changements biologiques amenant une dégradation de l'humeur et ultérieurement des comportements suicidaires chez les individus vulnérables a aussi été formulée (Volkow, 2001). D'autres auteurs supposent que le suicide et les problèmes de consommation de SPA auraient des facteurs de risques communs (Bukstein et al 1993 ;Rossow, Romelsjo & Leifman, 1999), par exemple des problèmes familiaux ou des abus physiques ou sexuels durant l'enfance (Mishara & Tousignant, 2004 ;Nadeau & Biron, 1998) ou certains traits de caractère comme l'impulsivité (Conason, Oquendo & Sher, 2006 ;Gossop, 2005 (Goldston, 2004).…”
Section: Introductionunclassified